THE IMPLEMENTATION OF INQUIRY BASED LEARNING IN TEACHING ENGLISH AT THE SEVENTH GRADE OF SMPN 2 COLOMADU IN 2014-2015 ACADEMIC YEAR - Nurjannah, Nisa; , Prof. Dr. Endang Fauziati, M. Hum; , Nur Hidayat, M.Pd (2015)
SUMMARY Nurjannah, Nisa. A320110117. THE IMPLEMENTATION OF INQUIRY BASED LEARNING IN TEACHING ENGLISH AT THE SEVENTH GRADE OF SMPN 2 COLOMADU IN 2014/2015 ACADEMIC YEAR. Research Paper. Muhammadiyah University of Surakarta. 2015. The objective of this study is to describe the implementation of Inquiry-based Learning in teaching English at first grade of SMPN 2 Colomadu in 2014-2015 academic year. The researcher gets the data of this research from event, informant and document. This research is a descriptive research. Analysis methods of collecting data are direct observation, interview and document. The techniques for analyzing data are reducing the data, displaying the data, and drawing conclusion, and also proposing suggestion. The results of the analysis show that: 1) For learning objective there are two kinds namely, general learning objective and specific learning objective. 2) In the learning cycle the researcher found that the teacher used Inquiry-based Learning in teaching English at 7H. There are three steps of teaching learning process in the class namely, pre-teaching, while-teaching and post-teaching. While-teaching consist of exploration, elaboration, and confirmation. 3) The techniques that researcher found during observation were oral repetition, reading passage, identifying key word, answering question, free writing, questioning, and summirizing. 4) There are seven roles of students at first grade of SMPN 2 Colomadu. Those roles are (a) the students as subject learning, (b) the students as object, (c) the students as performer, (d) students learns from the teacher , (e) the students learn from other students, (f)the students learns from other teaching sources, and (g) the students is monitor and evaluator of his or her own progress. 5) Teacher's role that researcher found in the learning process at 7H class of SMP N 2 Colomadu, they are: teacher as controller, teacher as manager, teacher as facilitator, teacher as resource and teacher as motivator. 6) The instructional material that is used in the teaching English at SMP N 2 Colomadu especially in 7H class they are: text book, picture, slide and video. And there are three roles of instructional material, they were: (a) as a source of activities for learner practice and communicative interaction,(b) a source of stimulation and ideas for classroom language activities, and (c) as a reference source for learners on grammar, vocabulary, pronunciation, etc. 7) Media, the researcher found five media which is used in teaching learning process at 7H grade in SMPN 2 Colomadu, such as, Picture, board, video, Power point, tape recorder. Keywords : Implementation, Inquiry-based Learning, Teaching English